2017
DOI: 10.5414/cn109019
|View full text |Cite
|
Sign up to set email alerts
|

New-onset hepatitis C virus-associated glomerulonephritis following sustained virologic response with direct-acting antiviral therapy

Abstract: Glomerulonephritis (GN) is an important extra-hepatic manifestation of infection with hepatitis C virus (HCV). HCV-associated GN occurs due to HCV-induced lymphoproliferation, leading to the generation of pathogenic immune complexes, including complexes containing cryoglobulins. The management of HCV-associated extra-hepatic disease is focused on viral eradication, with direct-acting antiviral agents leading to high rates of sustained virologic remission. There have been a few reports of relapsing cryoglobulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…disease has been noted by some authors in patients who achieved SVR with regimens based on DAAs [18][19][20]. Figure 2 shows purpuric manifestations in the lower limbs in a patient with HCV-related cryogobulinemic patient who received DAAs.…”
Section: Antiviral Treatment Of Hcv With Daas and Renal Impairmentmentioning
confidence: 79%
See 1 more Smart Citation
“…disease has been noted by some authors in patients who achieved SVR with regimens based on DAAs [18][19][20]. Figure 2 shows purpuric manifestations in the lower limbs in a patient with HCV-related cryogobulinemic patient who received DAAs.…”
Section: Antiviral Treatment Of Hcv With Daas and Renal Impairmentmentioning
confidence: 79%
“…Finally, we suggest that serum creatinine and urinary abnormalities should be monitored with accuracy in all patients after antiviral treatment with DAAs. New-onset or relapsing glomerular disease has been noted by some authors in patients who achieved SVR with regimens based on DAAs [18][19][20]. Figure 2 shows purpuric manifestations in the lower limbs in a patient with HCV-related cryogobulinemic patient who received DAAs.…”
Section: Antiviral Treatment Of Hcv With Daas and Renal Impairmentmentioning
confidence: 95%
“…Others have previously reported that persistent (n = 6), recurrent (n = 1), and even de novo (n = 2) HCV-CryoGN can occur despite achievement of SVR. 21 , 22 , 23 HCV-CryoGN in the setting of SVR may be an indication for immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…reported 2 patients with newly diagnosed HCV-CryoGN on kidney biopsy approximately 1 year after achieving SVR (1 patient with simeprevir and 1 patient with pegylated INF-α, ribavirin, and sofosbuvir). 22 Chowdhury and Tsen described a patient with recurrent HCV-CryoGN diagnosed approximately 2 months after achieving SVR with sofosbuvir and ribavirin. 23 We report herein 3 cases of biopsy-proven HCV-CryoGN diagnosed in patients who previously had achieved SVR with DAA therapy.…”
Section: Introductionmentioning
confidence: 99%
“…The development or persistence of cryoglobulinemic vasculitis (with or without kidney involvement) after achieving sustained virologic response has been described. [64][65][66][67] Whether this presentation reflects continued B-cell production of pathogenic immune complexes requires further study.…”
Section: C3 Glomerulopathiesmentioning
confidence: 99%